On deformations of pasting diagrams, II - Shrestha, Tej Bahadur; Yetter, David (My University, 2014)
We continue the development of the infinitesimal deformation theory of pasting diagrams of k-linear categories begun in TAC, Vol 22, #2. In that article the standard result that all obstructions are cocycles was established only for the elementary, composition-free parts of pasting diagrams. In the present work we give a proof for pasting diagrams in general. As tools we use the method developed by Shrestha of simultaneously representing formulas for obstructions, along with the corresponding cocycle and cobounding conditions by suitably labeled polygons, giving a rigorous exposition of the previously heuristic method; and deformations of pasting diagrams in which some cells are required to be deformed trivially.
Keywords: Pasting diagrams; Pasting schemes; Deformation theory